Physical and safety features of ablution spaces in the mosques of Selangor and Kuala Lumpur - Abdul Rahman, Julaila; Kamaruddin, Zumahiran; Abdullah, Mohd Hariri; Jasmani, Ismail; Ramli, Nurfadhila (Institute of Physics Publishing, 2018)
This study aims to explore the condition of physical and safety features of existing ablution platform and spaces of selected Malaysian mosques which are located in Kuala Lumpur and Selangor. Therefore, the objective of this study was to analyze the physical condition of ablution platforms and spaces focusing on the ergonomic aspects, user-friendly and safety features. Direct observation was conducted at the 15 selected mosques to examine the design aspects of the ablution platforms and spaces. The focus of analysis on the physical elements of the ablutions including design forms; ergonomic aspects, and safety features. The study found that most of the mosques have provided ablution seat with an ergonomic aspect; the appropriate size of seats and allocation of the water faucet. However, most of the mosques have their ablution areas with inappropriate distance among the seats and platform height. In addition, there is a lack of design consideration towards the needs of PwDs (Person with Disability) in providing the ablution platforms. These include the ablution area are not easily accessible and there is no special seats or area provided for PwDs to perform their ablution. This study recommends improving the ablution platform and spaces to be more user-friendly with ergonomic design and safety features to ensure the smoothness of ablution activity.